PENGEMBANGAN PARIWISATA DI KOTA TOMOHON - MOTOH, FABIOLA GRASELLA; LALOMA, ALDEN; LONDA, VERY (Sam Ratulangi University, 2021)
This study aims to determine the development tourism in Tomohon City. This type of research uses aqualitative descriptive method. Data collection techniques consisted of observation, interviews,documentation. The results showed that tourism development has been carried out through 3 activities init, namely increasing the development of suggestions and infrastructure, maintenance of tourist attractionfacilities as well as monitoring and evaluation. This is the main strategy for developing tourism objects bymaintaining strengths and optimizing opportunities while improving weaknesses and anticipating threatsthat exist in an effort to increase the number of tourist visits that can increase Tomohon. To increase theOriginal Regional Income of Tomohon City, It is hoped that the Government and the private sector, needto plan a marketing strategy so that the visiting tourists will continue to increase.Keywords: Development, Tourism, Tourism Objects.